Analysis of Factors Affecting Local Own-Source Revenue in Regency/City of Bali Province in 2010-2019 - Gladys Annisa Octavyanthi; Agus Tri Basuki (Universitas Muhammadiyah Yogyakarta, 2022)
Local own-source revenue (PAD) is one indicator to determine the independence of regional autonomy in exploring the potential to support sources of revenue. All regions are trying to increase PAD in their area by continuously increasing the potential found in their regions, and Bali Province is one of them. This research aims to analyze the effect of gross regional domestic product (GRDP), investment, and general allocation fund (DAU) on local own-source revenue in the regencies/cities of Bali Province in 2010-2019. Based on the analysis, the results obtained that jointly, all independent variables affected local own-source revenue. Individually or partially, the investment variable had a negative and insignificant effect on local own-source revenue. Meanwhile, the GRDP and general allocation fund (DAU) variables had a positive and significant impact on local own-source revenue in the regencies/cities of Bali Province.